FACTORS AFFECTING DELIVERY CARE OF URBAN MOTHERS: A CROSS-SECTIONAL STUDY OF THE URBAN PRIMARY HEALTH CARE PROJECT IN BANGLADESH - Md Mizanur Rahman; Sharmin Mizan; Razitasham Safii; Sk Akhtar Ahmad (The Indonesian Journal of Public Health, 2021)
Maternal mortality and its associated complications can be avoided by ensuring safe and supervised delivery. In this paper, the authors examined the factors associated with the utilisation of institutional delivery care at the Urban Primary Health Care Project (UPHCP) clinic in Bangladesh. A two-stage cluster sampling was used in selecting the ever-married women aged 15-49 years in the catchment areas of the UPHCP in Bangladesh. A total of 3,949 women’s data were analysed. The authors collected data through face-to-face interviews using a structured questionnaire. A multinomial logistic regression analysis was done to determine the potential factors associated with the utilisation of delivery care, in which ‘place of delivery care’ was considered as a dependent variable. Data entry and analysis were done in Statistical Package for the Social Sciences version 22.0. This study found that 30% of the women delivered their most recent child at the UPHCP clinic, and 45.9% of the women delivered their most recent child at other institutions. However, one-fifth of the women delivered at home. Doctors attended two-thirds of the deliveries. A small proportion of women were tended to by nurses, paramedics, FWV, and FWA. Traditional birth attendants attended one-fifth (20%) of deliveries. The multinomial logistic regression analysis found that respondents from poor catchment areas were 33.677 times more likely to utilise delivery care at the UPHCP when compared to 12.052 times by the respondents who took previous antenatal care from the non-poor catchment area. This study also found that women who had entitlement cards were 6.840 times more likely to utilise delivery care at the UPHCP in the poor catchment area, which was almost twice the women from the non-poor catchment area. Although the maternal mortality rate in Bangladesh has notably reduced,Bangladesh still needs to address the issue of safe delivery for marginalised women in order to attain the Sustainable Development Goals (SDGs) by 2030. A red card approach might increase access to the UPHCP for marginalised women to have safe deliveries.Keywords: poor, urban, red card, delivery care, Urban Primary Health Care Project, Bangladesh